If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -3m + 3m + -13 = 7m + -5m Reorder the terms: 1 + -13 + -3m + 3m = 7m + -5m Combine like terms: 1 + -13 = -12 -12 + -3m + 3m = 7m + -5m Combine like terms: -3m + 3m = 0 -12 + 0 = 7m + -5m -12 = 7m + -5m Combine like terms: 7m + -5m = 2m -12 = 2m Solving -12 = 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -12 + -2m = 2m + -2m Combine like terms: 2m + -2m = 0 -12 + -2m = 0 Add '12' to each side of the equation. -12 + 12 + -2m = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -2m = 0 + 12 -2m = 0 + 12 Combine like terms: 0 + 12 = 12 -2m = 12 Divide each side by '-2'. m = -6 Simplifying m = -6
| -2(x-3)-3(4x+3)=4 | | 2m^2+17m+10=0 | | 21-7x=-4(6x+4)-4(-5-4x) | | 4(8-y)=2y-4 | | -0.5x^2+20x+230=0 | | 9z=135 | | k=xy | | x^2+1=17 | | 3x/4=-6/7 | | (5x-1)/3=4 | | 30x+.70(150-x)=82.5 | | n+5=1037 | | (3+x)5-2=-17 | | (3+x)6=36 | | 87=4 | | 2x+3(3x-4)=6-7x | | 1/7(14r+28)=2(r+2) | | 4y^2+21y-18=0 | | 16-20=87t | | 14g+5=54 | | 4(2.75y)-y=10 | | 4y+21y-18=0 | | 30-18=4(x-7) | | -7+6x=-11 | | 4x-10.2=x | | 6r=30 | | 4x+-16=(x-4)+3 | | 2x+3+7x=3x+9 | | -2z=32 | | v+6=-6+3v | | 3x+32x-4=7(5x+2) | | h-7/6=1 |